Procalcitonin mediates vascular dysfunction in obesity - Brabenec, Laura; Hellenthal, Katharina E.M.; Müller, Melanie; Kintrup, Sebastian; Zurek-Leffers, Finnja; Kardell, Marina; Otto, Mandy; Wagner, Nana-Maria (Life sciences (1973), 2022)
Obesity is accompanied by a chronic low-grade inflammation associated with endothelial dysfunction and vascular complications. Procalcitonin is a marker of inflammation, secreted by adipose tissue and elevated in obese subjects. We here investigated whether visceral or perivascular fat-derived procalcitonin is a target to improve obesity-induced endothelial dysfunction. Procalcitonin expression was identified by Western blot. Murine endothelial cells were isolated using CD31-antibody-coated magnetic beads and reactive oxygen species and nitric oxide (NO) determined by H2DCF- or DAF-FM diacetate loading. Endothelium-dependent vasorelaxation was analyzed using pressure myography of murine arterioles. Calcitonin gene-related peptide (CGRP) was used to activate the calcitonin receptor-like receptor (CRLR)/RAMP1 complex and olcegepant or the dipeptidyl-peptidase 4 (DPP4) inhibitor sitagliptin to block procalcitonin signaling or activation. In addition to visceral adipose tissue, procalcitonin was present in perivascular and epicardial tissue. In concentrations typical for obesity, procalcitonin doubled reactive oxygen species formation and decreased endothelial nitric oxide production in murine endothelial cells. Intravenous delivery of procalcitonin to mice in obesity-associated concentrations impaired endothelium-dependent vasorelaxation in a CRLR/RAMP1-dependent manner and antagonized CGRP-induced endothelial NO release in vitro. Use of CRLR/RAMP1-receptor antagonist olcegepant counteracted procalcitonin effects on vasodilation, nitric oxide production and reactive oxygen species formation. Similarly, blocking procalcitonin activation by the DPP4 inhibitor sitagliptin antagonized endothelial procalcitonin effects. Procalcitonin, liberated either from visceral or perivascular adipose tissue, contributes to endothelial dysfunction by antagonizing CGRP signaling in obesity. Targeting hyperprocalcitonemia may be a means to preserve endothelial function and reduce comorbidity burden in obese subjects. Schematic illustration of the proposed mechanism. Under healthy conditions, procalcitonin levels are low. CGRP binds to the CRLR/RAMP1 receptor complex, inducing nitric oxide production and subsequent vasodilation (left panel). Obesity causes an increase in procalcitonin levels due to procalcitonin release from low-grade inflamed visceral and perivascular adipose tissue. Procalcitonin antagonizes CGRP at the CRLR/RAMP1 complex and further impairs vasodilatation by reducing NO bioavailability and increasing ROS production (right panel). Created with BioRender.com. [Display omitted]